Self-Regulated Learning Among College Students Who Are Working as Part-Timers: Is It Necessary? - Andya, Winna Rafaella; Sulastri, Augustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Students who have the dual role of studying while working usually do not have more time to study compared to students who only attend lectures. The fact that college students face difficulties managing their time for study and work shows that they have a low level of self-regulation learning. This study aims to find out whether there is a relationship between learning motivation and self-regulated learning of students who take courses while working part-time with independent study. This study involved 117 respondents who worked part-time as respondents. A correlational quantitative approach is used. The data collected for the study was collected through purposive sampling techniques using data analysis using the Product-Moment Correlation Technique. The study found a correlation coefficient value r = 0.232 and a p value of 0.012 (p < 0.05), this study has proven a positive and significant relationship. The study also found aspects of willingness to understand and master, commitment to duties and obligations, and initiative related to self-regulated learning. The results of the analysis and discussion showed that learning motivation has a positive relationship with self-regulated learning in students who work part-time.Mahasiswa yang memiliki peran ganda berkuliah sambil bekerja biasanya tidak memiliki lebih banyak waktu untuk belajar dibandingkan dengan mahasiswa yang hanya mengikuti perkuliahan. Fakta bahwa mahasiswa menghadapi kesulitan untuk mengatur waktu mereka untuk belajar dan bekerja menunjukkan bahwa mereka memiliki tingkat self-regulation learning yang rendah. Studi ini bertujuan untuk mengetahui apakah ada hubungan antara motivasi belajar dan self-regulated learning mahasiswa yang mengambil kuliah sambil bekerja part-time dengan belajar secara mandiri. Penelitian ini melibatkan 117 responden yang bekerja part-time sebagai responden. Pendekatan kuantitatif korelasional digunakan. Data yang dikumpulkan untuk penelitian dikumpulkan melalui teknik purposive sampling menggunakan analisis data menggunakan Teknik Korelasi Product-Moment. Kajian menemukan nilai koefisien korelasi r = 0.232 dan nilai p 0,012 (p < 0.05), penelitian ini telah membuktikan adanya hubungan positif dan signifikan. Kajian juga menemukan aspek keinginan memahami dan menguasai, komitmen akan tugas dan kewajiban, dan inisiatif berhubungan dengan self-regulated learning. Hasil analisis dan diskusi menunjukkan bahwa motivasi belajar memiliki hubungan positif dengan self-regulated learning pada mahasiswa yang bekerja part-time.